The participation of people with dementia in the planning of their care and support: An integrative literature review - Read, S.; Toye, Christine; Wynaden, Dianne (Sage Publications Ltd., 2018)
Background: People with dementia continue to voice concerns that health professionals are reluctant to engage with them about the planning of their care and support. Instead, their perspective is that such plans are often made by others and fail to reflect their wishes. Objective: This review aimed to examine investigations of the participation of people living with dementia in the planning of their care and support, when they have also provided study data. Methods: An integrative literature review was conducted to identify, critique, and synthesise relevant research findings. Eight electronic databases were searched to identify peer reviewed journal articles that met inclusion criteria. In addition, reference lists of included articles were searched, and a subject expert was consulted about any possible omissions. Results: From the 346 articles accessed, seven met inclusion criteria for review. The quality appraisal showed that one article reported only pilot data; several more reported small sample sizes; and, in two instances, there was a lack of information about the psychometric properties of data collection tools and about recruitment and attrition rates. Conclusions: There has been limited investigation of the participation of people with dementia in the planning of their support when they have also contributed research data. Findings provide some evidence of their participation by attending education programme, setting goals in cognitive rehabilitation therapy and contributing to advance care planning.